PERMINTAAN BAMBU KONSTRUKSI PADA OUTLET PENJUAL BAMBU DI KELURAHAN KINILOW KECAMATAN TOMOHON UTARA - Anita S. Safisa; Hengki D. Walangitan; Paulus A. Pengemanan (Universitas Sam Ratulangi, 2017)
ABSTRACTÂ The research aims to identify the quantity of demand and marketing outlets bamboo constuction in the bamboo sales outlets in Kinilow urban village. The research used interview method with the tools of the questionnaire for 4 respondents. The result of research showed that in general, the quantity of demand basically very fluctuated. The size demand of bamboo construction was difficult to set, but stock of bamboo keep provided all the time. Estimated within a week of bamboo construction available approximately as much as 1000 tips. The quantity of bamboo construction demands each month ranges from 750 to 1000 tips. Construction bamboo producers that was too small had very simple marketing outlets. There were 2 marketing outlets, (1) the farmers (producers) sold to consumers directly. (2) the farmers (producers) sold to collectors and then the collectors sold to consumers.Â Keywords : Bamboo Construction, Demand, Marketing Outlets, Kinilow urban village